Bromance as a Masquerade: Adaptation and Reception of Chinese Danmei Fantasy / Броманс как маскарад: адаптация и рецепция китайских фэнтези в жанре данмей - NIM EVGENIYA G. / НИМ Е.Г. (Наука телевидения, 2022)
The article discusses danmei (or boys love, BL), a fiction genre which occupies a special place in Chinese pop culture. Despite the fact that these entertainment stories are characterized by a love line between male characters, the authors and consumers of Chinese BL are primarily heterosexual women. Danmei has become popular not only in China itself, but also in many other countries, which adds relevance to the study of its reception by the Russian audience. First of all, this applies to web series television adaptations of network BL novels available to the world audience. The research focuses on a number of issues related to the production, adaptation, and consumption of danmei media content. What are the features of the genre and how does it differ from non-Chinese versions of BL? What makes danmei so attractive for women and how is the Chinese BL community structured? What strategies does the Chinese web series industry use to adapt primary sources and how do BL fans and a wider audience perceive these adaptations? The article shows the contradictions inherent in the danmei subculture: on the one hand, its proximity to the feminist and queer movements, on the other—its support for heteropatriarchal values. Special attention is paid to the analysis of the representative strategy of bromance used by Chinese producers in the TV adaptations of danmei novels under party-state censorship. In particular, I analyze the popular TV series S.C.I. Mystery (2018), Guardian (2018), The Untamed (2019), and Word of Honor (2021). Apart from de-erotizing the interactions of between the protagonists, these adaptations significantly modify the genre, plot, setting, and characters. At the same time, producers of the shows take into account the expectations of the multimillion army of danmei fans, leaving them certain opportunities for queer reading. In Russia, danmei by the web novelist Mo Xiang Tong Xiu are the most popular, as well as the fantasy web series The Untamed based on her novel Mo Dao Zu Shi. This case study of the multi-part online drama The Untamed reveal the three patterns of reception of the series by the Russian audience: bromantic, romantic and “fluid.” In conclusion, the challenges of conceptualizing danmei as a genre, subculture, and entertainment industry have been articulated. В статье рассматриваются романтические фэнтези в жанре данмей (или boys love, BL), занимающие особое место в китайской поп-культуре. Для развлекательных историй подобного типа характерна любовная линия между мужскими персонажами, в то время как создателями и потребителями китайского BL являются прежде всего гетеросексуальные женщины. Данмей стал популярен не только в самом Китае, но и во многих странах мира, что делает актуальным изучение его рецепции российской аудиторией. Прежде всего это касается веб-сериалов — телевизионных адаптаций сетевых BL-новелл, доступных для просмотра мировому зрителю. Исследование сфокусировано на ряде вопросов, связанных с процессами производства, адаптации и потребления медийного контента в жанре данмей. В чем состоят особенности жанра и его отличие от не-китайских версий BL? Что мотивирует женщин к увлечению данмей и как устроено китайское BL-сообщество? Какие стратегии адаптации первоисточников использует китайская индустрия веб-сериалов и как поклонники BL и более широкая аудитория воспринимают эти экранизации? В статье показаны противоречия, присущие субкультуре данмей: с одной стороны, ее близость феминистскому и квир-движению, с другой — поддержка гетеропатриархальной системы ценностей. Особое внимание уделено анализу репрезентативной стратегии броманса, используемой китайскими продюсерами при телеадаптации данмей-новелл в условиях партийно-государственной цензуры. В частности, рассматриваются популярные сериалы «S.C.I. Коллекция загадочных дел» (2018), «Хранитель» (2018), «Неукротимый: повелитель Чэньцин» (2019) и «Далекие странники» (2021). Помимо деэротизации взаимодействий двух главных протагонистов, этим экранизациям присуща заметная модификация жанра, сюжета, сеттинга и персонажей. В то же время производители шоу учитывают ожидания многомиллионного фэндома, оставляя поклонникам данмей определенные возможности для квир-прочтения. В России наиболее известны BL-новеллы сетевой писательницы Мосян Тунсю, а также фэнтезийный сериал «Неукротимый: повелитель Чэньцин», снятый по ее роману Mo Dao Zu Shi. В результате проведенного кейс-стади многосерийной онлайн-драмы «Неукротимый» были выявлены три паттерна рецепции сериала российским зрителем: бромантический, романтический и «флюидный». В заключении артикулируются сложности концептуализации данмей как жанра, субкультуры и индустрии развлечений.